(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2015)
For visual documents that occur within the family or are related to an individual’s life, which also show exceptional moments during the flow of time of a family, or this concerns the rites of passage (wedding, childbirth, baptism, children’s birthdays, death, etc.), it is being considered that that type of matter represents the ideal picture of a person or his family. But, in regards to the research of photography, we will take into consideration its communication aspect. The emphasis is placed on the experience gained during my own field researches, when the subject of interest were the rites of the family cycle, especially the wedding, but also the rites of baptism, childbirth, when these moment were told to me numerous times with the help of photography. The glorious relationship that existed between the photo and the opportunity it offered for making a photo-story was especially emphasized when the narrators carefully took out their preserved photographs. The fast development of photography is characterized with the emergence of the family photo-albums, which were originally classified following the history of life, following the themes of the main phases of a life cycle. In this context, we might mention family albums with pictures of new-borns, christening, weddings, etc.